Bismuth-based glass powder and composite powder including the same
A bismuth-based glass powder with controlled composition and additives addresses thermal instability and crystallization issues, ensuring high thermal stability and effective sealing for low-expansion members.
Patent Information
- Application Number
- JP2024040695
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-12
- Filing Date
- 2024-03-15
- Publication Date
- 2025-01-24
AI Technical Summary
Bismuth-based glass powders exhibit low thermal stability and crystallization issues during firing, compromising their suitability for low-expansion members, and reducing low-melting point components to improve stability undermines their sealing characteristics.
A bismuth-based glass powder composition comprising specific ratios of Bi2O3, TeO2+CuO, ZnO, B2O3, BaO, Al2O3, and optional additives like Fe2O3, SiO2, Li2O, Na2O, K2O, P2O5, Y2O3, and CeO2, with controlled softening points and thermal expansion coefficients, combined with a fire-resistant filler to enhance thermal stability and mechanical strength.
The composition maintains low-melting characteristics while achieving high thermal stability, reducing crystallization, and ensuring effective sealing and mechanical integrity of low-expansion members.
Smart Images

Figure 2025013141000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a bismuth-based glass powder and a composite powder using the same, and more particularly to a bismuth-based glass powder suitable for low-temperature sealing of low-expansion members and a composite powder using the same. [Background technology]
[0002] Glass powder made of low-melting glass is used to seal low-expansion materials (e.g., AlN, silicon, non-alkali glass, etc.). The low-melting glass is required to have properties such as chemical durability, mechanical strength, and electrical insulation depending on the application.
[0003] As a low-melting glass that satisfies these required properties, lead-based glass containing a large amount of PbO has been widely used (see Patent Document 1).
[0004] However, PbO has a problem of being a heavy environmental load. For this reason, replacement of lead-based glass with lead-free glass is desired, and various lead-free glasses have been developed. In particular, the bismuth-based glass described in Patent Document 2 and the like has a low melting point and is therefore a promising candidate to replace lead-based glass. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 63-315536 [Patent Document 2] JP 2000-128574 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, the above-mentioned bismuth-based glass has a problem in that it has low thermal stability and bismuth-based crystals are precipitated during firing (sealing).
[0007] In order to improve the thermal stability, it is effective to reduce the content of low-melting point components in the bismuth-based glass. However, in this case, the low-melting point characteristics cannot be maintained and the firing temperature increases to, for example, above 500°C, resulting in thermal degradation of the low-expansion member.
[0008] The present invention has been made in view of the above circumstances, and has an object to provide a bismuth-based glass powder that has high thermal stability while maintaining a low melting point characteristic. [Means for solving the problem]
[0009] As a result of various experiments, the present inventors have found that the above problems can be solved by using a bismuth-based glass powder having a specific composition. Hereinafter, various aspects of the bismuth-based glass powder and composite powder that solve the above problems will be described.
[0010] The bismuth-based glass powder of the first aspect is characterized in that the glass composition contains, in mole percent, 41-60% Bi2O3, 2-15% TeO2+CuO, 17-30% ZnO, 10-30% B2O3, 3-9% BaO, and 0.7-10% Al2O3, where "TeO2+CuO" refers to the total amount of TeO2 and CuO.
[0011] The bismuth-based glass powder of the second aspect preferably has a softening point of 440° C. or less in the first aspect. Here, the "softening point" is a value measured by a macro-type differential thermal analysis (DTA) device. DTA is performed in air at a heating rate of 10° C. / min, and the measurement is started from room temperature.
[0012] The composite powder of the third embodiment preferably contains the bismuth-based glass powder of the first or second embodiment and a refractory filler.
[0013] In the composite powder of aspect 4, in aspect 3, the content of the fire-resistant filler is preferably 1 to 30 mass %.
[0014] The composite powder of the fifth aspect is the composite powder of the third or fourth aspect, wherein the linear thermal expansion coefficient is 40×10 -7 / ℃ or more and 80×10 -7 / °C or less. Here, the "linear thermal expansion coefficient of the composite powder" is a value measured using a dense sintered body as a measurement sample in a temperature range of 30 to 250°C with a push rod type linear thermal expansion measurement (TMA) device.
[0015] The composite powder of the sixth embodiment is preferably used for sealing in any one of the third to fifth embodiments. Effect of the Invention
[0016] According to the present invention, it is possible to provide a bismuth-based glass powder that has high thermal stability while maintaining a low melting point characteristic. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The bismuth-based glass powder of the present invention is characterized by the glass composition containing, in mole percent, 41-60% Bi2O3, 2-15% TeO2+CuO, 17-30% ZnO, 10-30% B2O3, 3-9% BaO, and 0.7-10% Al2O3. The reasons for limiting the glass composition as described above are as follows. In the following description of the content ranges, the % indication refers to mol%.
[0018] Bi2O3 is a main component that lowers the softening point and also enhances water resistance and weather resistance. The content of Bi2O3 is 41 to 60%, preferably 42 to 55%, and more preferably 43 to 50%. If the content of Bi2O3 is low, the softening point becomes too high, making it difficult to soften and flow in a temperature range of 500°C or less, and sealing defects and the like are likely to occur. On the other hand, if the content of Bi2O3 is high, the linear thermal expansion coefficient increases, and residual stress tends to become excessive after sealing of low expansion members (e.g., AlN, silicon, non-alkali glass, etc.). In addition, thermal stability (devitrification resistance) tends to decrease, and crystals such as bismite tend to precipitate.
[0019] TeO2 is a component that forms a glass network of bismuth-based glass. It is also a component that enhances thermal stability and suppresses reduction of Bi2O3. The content of TeO2 is preferably 1 to 15%, more preferably 2 to 10%, and even more preferably 3 to 8%. If the content of TeO2 is small, the thermal stability decreases, and crystals such as bismite tend to precipitate during firing. On the other hand, if the content of TeO2 is large, the softening point becomes too high, making it difficult to soften and flow in a temperature range of 500°C or less, and sealing defects and the like tend to occur. In addition, devitrification tends to occur during glass molding.
[0020] CuO is a component that enhances thermal stability and inhibits reduction of Bi2O3. The content of CuO is preferably 1 to 15%, more preferably 2 to 10%, and further preferably 3 to 8%. If the content of CuO is small, the thermal stability decreases, and crystals such as bismite are likely to precipitate during firing. On the other hand, if the content of CuO is large, the softening point becomes too high, making it difficult for the glass to soften and flow in a temperature range of 500°C or less, and sealing defects and the like are likely to occur. In addition, the glass is likely to devitrify during molding.
[0021] TeO2+CuO (total amount of TeO2 and CuO) is 2 to 15%, preferably 2.5 to 10%, and more preferably 3 to 8%. If the amount of TeO2+CuO is small, the thermal stability decreases, and crystals such as bismite tend to precipitate during firing. On the other hand, if the amount of TeO2+CuO is large, the softening point becomes too high, making it difficult to soften and flow in a temperature range of 500°C or less, and sealing defects tend to occur. In addition, devitrification tends to occur during glass molding.
[0022] ZnO is a component that reduces the linear thermal expansion coefficient. It is also a component that suppresses devitrification caused by TeO2 during glass molding. The content of ZnO is 17 to 30%, preferably 18 to 27%, and more preferably 19 to 25%. If the content of ZnO is low, the linear thermal expansion coefficient increases, and residual stress tends to become excessive after sealing of the low expansion member. Also, devitrification tends to occur during glass molding. This devitrified material tends to remain after sealing and deteriorate the sealing characteristics. On the other hand, if the content of ZnO is high, thermal stability tends to decrease.
[0023] B2O3 is a component that forms a glass network of bismuth-based glass. The content of B2O3 is 10 to 30%, preferably 15 to 27%, and more preferably 18 to 25%. If the content of B2O3 is low, the thermal stability is likely to decrease. On the other hand, if the content of B2O3 is high, the softening point becomes too high, making it difficult to soften and flow in a temperature range of 500°C or less, and sealing defects and the like are likely to occur.
[0024] BaO is a component that enhances thermal stability. The content of BaO is 3 to 9%, preferably 3.5 to 8.5%, and more preferably 4 to 8%. When the content of BaO is small, the thermal stability is likely to decrease. On the other hand, when the content of BaO is large, the softening point becomes too high, making it difficult for the material to soften and flow in a temperature range of 500°C or less, and sealing defects and the like are likely to occur.
[0025] Al2O3 is a component that suppresses devitrification during glass molding and enhances thermal stability. The content of Al2O3 is 0.7 to 10%, preferably 0.8 to 5%, and more preferably 1 to 3%. If the content of Al2O3 is small, the thermal stability is likely to decrease. On the other hand, if the content of Al2O3 is large, the softening point becomes too high, making it difficult for the glass to soften and flow in a temperature range of 500°C or less, and sealing defects and the like are likely to occur.
[0026] In addition to the above components, the following components may be added:
[0027] Fe2O3 is a component that enhances thermal stability and inhibits the reduction of Bi2O3. The content of Fe2O3 is preferably 0 to 2%, more preferably 0 to 1.5%, and further preferably 0.1 to 1%. If the content of Fe2O3 is high, the glass becomes more susceptible to devitrification.
[0028] SiO2 is a component that enhances water resistance and weather resistance, but also significantly increases the softening point. Therefore, the content of SiO2 is preferably less than 1%, more preferably less than 0.5%, and even more preferably less than 0.1%.
[0029] Li2O, Na2O and K2O are components that lower the softening point but also have the effect of promoting devitrification, so the total and individual contents of Li2O, Na2O and K2O are preferably 2% or less, more preferably less than 0.5%, and even more preferably less than 0.1%.
[0030] P2O5 is a component that enhances thermal stability, but if its content is high, it tends to promote phase separation of glass. Therefore, the content of P2O5 is preferably 2% or less, more preferably less than 0.5%, and even more preferably less than 0.1%.
[0031] MoO3, Y2O5 and CeO2 are components that enhance thermal stability, but if their contents are too high, the softening point becomes too high, making it difficult for the material to soften and flow in a temperature range of 500°C or less, and prone to occurrence of poor sealing, etc. Therefore, the combined and individual contents of MoO3, Y2O5 and CeO2 are preferably 2% or less, more preferably less than 0.5%, and even more preferably less than 0.1%.
[0032] For environmental reasons, it is preferred that the glass is substantially free of PbO, i.e., contains less than 0.1% PbO. Also, the addition of PbO to the glass composition increases the amount of PbO in the glass when used as an insulator. 2+ may diffuse, resulting in a decrease in electrical insulation.
[0033] In addition to the above components, other components (MgO, CaO, SrO, etc.) may be added up to 5%.
[0034] The bismuth-based glass powder of the present invention preferably has the following characteristics:
[0035] The linear thermal expansion coefficient of the bismuth-based glass powder is preferably 80×10 -7 / ℃ or more and 130×10 -7 / ℃ or less, more preferably 90×10 -7 / ℃ or more and 125×10 -7 / °C or less. If the linear thermal expansion coefficient of the bismuth-based glass powder is outside the above range, it becomes difficult to reduce the linear thermal expansion coefficient of the composite powder even if a refractory filler is added. In the present invention, the "linear thermal expansion coefficient" is a value measured by a TMA device in a temperature range of 30 to 250°C using a bulk sample as a measurement sample.
[0036] The softening point of the bismuth-based glass powder is preferably 390 to 440° C., more preferably 395 to 430° C. If the softening point of the bismuth-based glass powder is too low, the content of Bi2O3 in the glass composition tends to be high, and in this case, the thermal stability is likely to decrease. On the other hand, if the softening point of the bismuth-based glass powder is too high, the firing temperature is likely to increase unduly.
[0037] Average particle size of bismuth glass powder D 50 The average particle diameter D of the bismuth-based glass powder is preferably less than 5 μm, 0.5 to 4 μm, and particularly 1 to 3 μm. 50 If the average particle diameter D of the bismuth-based glass powder is large, the softening point of the bismuth-based glass powder is difficult to lower. 50 If the average particle diameter D is small, it becomes difficult to handle. 50 " indicates a value measured on a volume basis by a laser diffraction method.
[0038] The composite powder of the present invention preferably contains the above-mentioned bismuth-based glass powder and a refractory filler. The bismuth-based glass powder is a component that softens and deforms during firing to hermetically integrate low expansion members and the like. The refractory filler is a component that acts as an aggregate and increases the mechanical strength of the composite powder while decreasing the thermal expansion coefficient of the composite powder. In addition to the bismuth-based glass powder and the refractory filler, the composite powder may contain a pigment or the like to improve visibility.
[0039] The content of the refractory filler is preferably 1 to 30 mass%, more preferably 10 to 27 mass%, and further preferably 13 to 24 mass%. If the content of the refractory filler is less, the effect of adding the refractory filler is reduced, while if the content of the refractory filler is more, the softening fluidity of the composite powder is likely to decrease, and further, a part of the refractory filler is dissolved in the glass during firing, which makes the glass more likely to devitrify.
[0040] As the refractory filler, powders of willemite ceramics, β-eucryptite, cordierite, zircon ceramics, tin oxide ceramics, zirconium phosphate ceramics, mullite, quartz glass, alumina, etc. can be used alone or in combination. Among them, cordierite is preferred because it has good compatibility with bismuth glass and is highly effective in reducing the linear thermal expansion coefficient.
[0041] The linear thermal expansion coefficient of the composite powder is preferably 40×10 -7 / ℃ or more and 80×10 -7 / ℃ or less, more preferably 45×10 -7 / ℃ or more and 70×10 -7 / ° C. or less. If the linear thermal expansion coefficient of the composite powder is outside the above range, the residual stress tends to become excessive after sealing with a low expansion member (for example, AlN, silicon, non-alkali glass, etc.).
[0042] The firing temperature in the atmosphere is preferably 500°C or less, more preferably 490°C or less. If the firing temperature is too high, there is a risk of thermal degradation of the low expansion member and its surrounding members. Here, the "firing temperature" is evaluated by a flow button test. In detail, a powder having a mass equivalent to the specific gravity is dry-pressed into a button shape with an outer diameter of 20 mm using a mold, and then this button is placed on an alkali-free glass substrate and fired at various firing temperatures. The diameter of the fired button (flow button) is measured, and the minimum temperature at which the diameter exceeds 20 mm is defined as the firing temperature. The firing is performed by increasing the temperature from room temperature to the firing temperature at a rate of 10°C / min, holding the firing temperature for 10 minutes, and then decreasing the temperature from the firing temperature to room temperature at a rate of 10°C / min.
[0043] The composite powder of the present invention can be made into a paste by adding a vehicle, thereby dramatically improving the coating workability and the like.
[0044] The vehicle mainly consists of a solvent and a resin binder, and the resin binder is added to adjust the viscosity of the paste. If necessary, a surfactant, a thickener, etc. can also be added. The prepared paste is usually applied to a substrate or the like using a coater such as a dispenser or a screen printer, and then subjected to a binder removal process.
[0045] As the resin binder, acrylic acid esters (acrylic resins), ethyl cellulose, polyethylene glycol derivatives, nitrocellulose, polymethylstyrene, polyethylene carbonate, methacrylic acid esters, and the like can be used.
[0046] Examples of the solvent that can be used include N,N'-dimethylformamide (DMF), α-terpineol, higher alcohols, γ-butyl lactone (γ-BL), tetralin, butyl carbitol acetate, ethyl acetate, isoamyl acetate, diethylene glycol monoethyl ether, diethylene glycol monoethyl ether acetate, benzyl alcohol, toluene, 3-methoxy-3-methylbutanol, triethylene glycol monomethyl ether, triethylene glycol dimethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monobutyl ether, tripropylene glycol monomethyl ether, tripropylene glycol monobutyl ether, propylene carbonate, dimethyl sulfoxide (DMSO), and N-methyl-2-pyrrolidone. In particular, α-terpineol is preferred because it has high viscosity and good solubility in resin binders and the like.
[0047] The composite powder of the present invention may be processed into a sintered body having a predetermined shape, so that it can be stably arranged in the area to be sealed.
[0048] The sintered body can be produced by adding a vehicle to the composite powder, granulating the mixture using a spray dryer or the like, pouring the resulting granules into a mold and press-molding the mixture to produce a pressed body, and then sintering the pressed body.
[0049] The composite powder of the present invention has a low linear thermal expansion coefficient and excellent softening fluidity, and is therefore preferably used for sealing low expansion members (e.g., AlN, silicon, non-alkali glass, etc.). In addition to sealing applications, the composite powder of the present invention is also preferably used for insulating coating of low expansion members. EXAMPLES
[0050] The present invention will be described in detail below based on examples.
[0051] Table 1 shows examples of the present invention (samples Nos. 1 to 5) and comparative examples (samples Nos. 6 and 7).
[0052] [Table 1]
[0053] Each sample in Table 1 was prepared as follows. First, a glass batch was prepared by mixing raw materials such as various oxides and carbonates so as to obtain the glass composition shown in the table, and this was placed in a platinum crucible and melted at 1000°C for 2 hours. Next, a portion of the molten glass was poured into a stainless steel mold as a sample for measuring the linear thermal expansion coefficient, and the remaining molten glass was formed into a film using a water-cooled roller. Finally, the film-like glass was pulverized using a ball mill or a mortar and pestle mill, and then air-classified to determine the average particle diameter D 50 A bismuth-based glass powder of about 3.0 μm was obtained.
[0054] The linear thermal expansion coefficient of the bismuth-based glass powder was measured by measuring the linear thermal expansion coefficient of the above-mentioned sample in the temperature range of 30 to 250° C. using a TMA device.
[0055] The softening point of the bismuth-based glass powder was measured using a macro-type DTA device. The measurement was performed in air at a temperature increase rate of 10° C. / min, starting from room temperature.
[0056] Next, the bismuth-based glass powder and the cordierite powder (referred to as CDR in the table) were mixed in the mass ratio shown in the table to prepare a composite powder. The average particle diameter D 50 2.0μm, 99% particle size D 99 was set to 8.0 μm.
[0057] The linear thermal expansion coefficient of the composite powder was measured by using a dense sintered body as a measurement sample in a temperature range of 30 to 250°C with a TMA device.
[0058] The firing temperature was evaluated by a flow button test. More specifically, a composite powder with a mass equivalent to the specific gravity was dry-pressed into a button with an outer diameter of 20 mm using a mold, and then the button was placed on an alkali-free glass substrate (OA-10G manufactured by Nippon Electric Glass Co., Ltd.) and fired at various firing temperatures. The diameter of the fired button (flow button) was measured, and the minimum temperature at which the diameter exceeded 20 mm was defined as the firing temperature. In measuring the firing temperature, the temperature was raised from room temperature to the firing temperature at a rate of 10°C / min, held at the firing temperature for 10 minutes, and then lowered from the firing temperature to room temperature at a rate of 10°C / min.
[0059] The surface condition after firing was evaluated by observing the buttons after firing at the above firing temperatures. Those in which no crystal precipitation was observed were rated as "O" and those in which crystal precipitation was observed were rated as "X".
[0060] As is clear from the table, in samples Nos. 1 to 5, the glass composition is restricted to a predetermined range, so that the linear thermal expansion coefficient is 61×10 -7 / °C or less, and the firing temperature was 490°C or less. Furthermore, the surface condition after firing was evaluated as Good. On the other hand, sample No. 6 did not contain TeO2 or CuO in the glass, so bismite crystals precipitated during firing, and the surface condition after firing was evaluated as Poor. Sample No. 7 did not contain ZnO in the glass, so it devitrified during glass molding, and the devitrified matter remained after firing, and the surface condition after firing was evaluated as Poor.
Claims
1. The glass composition is, in mol%, Bi 2 O 3 41-60%, TeO 2 +CuO 2-15%, ZnO 17-30%, B 2 O 3 10-30%, BaO 3-9%, Al 2 O 3 A bismuth-based glass powder containing 0.7 to 10% of bismuth.
2. 2. The bismuth-based glass powder according to claim 1, characterized in that it has a softening point of 440° C. or lower.
3. A composite powder comprising the bismuth-based glass powder according to claim 1 or 2 and a refractory filler.
4. 4. The composite powder according to claim 3, characterized in that the content of the refractory filler is 1 to 30 mass %.
5. Linear thermal expansion coefficient is 40 x 10 -7 / ℃ or more and 80×10 -7 4. The composite powder according to claim 3, wherein the temperature is 0.1 to 100° C.
6. 4. The composite powder according to claim 3, which is used for sealing.
Citation Information
Patent Citations
Frit for low-temperature sealing
JP1988315536A
Bismuth-based glass composition
JP2000128574A